Quality improvement on reducing neonatal mortality through intensive Clinical Mentorship Intervention: a case study in Biak Regional Hospital, Papua-Indonesia - Rinawati Rohsiswatmo; Windhi Kresnawati; Liza Froulina; Bobby Marwal Syahrizal; Nurlely Bethesda Sinaga; Edit Oktavia Manuama; Setya Wandita (BMJ Open Quality)
Background The neonatal mortality rate in Papua Province of Indonesia is unacceptably high. To address the issue, the Ministry of Health and UNICEF Indonesia initiated a hospital mentoring programme from 2014 to 2016 to improve the quality of care and health workers’ capacity to provide neonatal care. This study aimed to assess the impact of hospital mentoring on neonatal mortality.Methods The study was conducted at Biak District Hospital, Indonesia. The neonatal mortality was compared for three periods: preintervention (2011–2013), mentorship intervention phase (2014–2016) and postintervention (2017–2020). The mentoring programme is a combination of a direct-intensive-regular mentoring process and a scholarship programme for paediatricians. In the mentoring process, paediatricians, neonatal nurses and electromedical staff from national hospitals were sent to train the nurses on nursing management for sick neonates, clinical neonatal resuscitation, stabilisation and transportation. The neonatal mortality data were collected from birth registers, medical records, death case review reports and mentoring programme reports.Results A significant decrease in the percentage of death cases before 24 hours of hospitalisation and death cases due to asphyxia was observed in the three periods. In the death cases from referrals, a significant decrease from 70% in the intervention period to 39.7% in the postintervention period was observed (p<0.05). The survival rate of neonates with body weights under 1500 g and 1500–2500 g was compared in the intervention and postintervention period, a significant increase from 21% to 58% and 55% to 94% was observed, respectively (p<0.05).Conclusion The direct-intensive-regular mentoring intervention programme was found to be effective in reducing neonatal mortality through quality improvement in low-resource district hospitals.